Comparison study on shear strength and intermetallic compound for SAC and polymer core solder balls - Kar Y.B.; Agileswari; Hui T.C.; Talik N.A. (2023)
Solder joint strength on lead-free product is a reliability concern when subjected to the different environment stress in comparison to leaded product. Integrating a lead-free polymer core inside the solder ball may be a good strategy, where the polymer core could function as a stress buffer to dissipate stress better compared to purely metallic Sn3.8Ag0.7Cu (SAC 387) solder ball which is widely in use currently in the semiconductor field. In this research work, the effect of Intermetallic Compound (IMC) growth and solder ball shear strength were observed under multiple reflow up to 5 times and High Temperature Storage (HTS) stress tests in comparison to the both polymer core and SAC 387 solder ball. The IMC thickness was observed under high power scope with magnification 50 via the mechanical cross-section and the solder ball shear was conducted via the Dage 4000 series bond tester orm the shear strength. However, the shear strength is lowest out HTS 504 hours for polymer core solder ball. This could be due to the Kirkendall voids that started forming and causing cracks between the interface of copper and solder. It is because the diffusion rate of the copper (Cu) is faster than the diffusion rate of Tin (Sn). Hence, this could affect the solder joint strength and resulting in thicker IMC layer especially when subjected to HTS stress. From this research, it can be concluded that the polymer core solder ball demonstrates higher shear strength than SAC 387 solder ball in multiple reflow. Nevertheless, the shear strength is low in HTS 144 and 504 hours due to excessive of Kirkendall voids, causing poor joint strength performance. Further study would be recommended with an additional Nickel (Ni) layer coated on copper to reduce the Kirkendall voids in order to provide better reliability performance as Ni could function as diffusion barrier to prevent faster diffusion from Cu to Sn. 2013 American Scientific Publishers All rights reserved.